THE IMPACT OF PLATELET-RICH PLASMA (PRP) INJECTION TECHNIQUE ON THE RANGE OF MOTION AND PAIN LEVELS IN BASKETBALL PLAYERS WITH ROTATOR CUFF INJURIES - Assist. Prof. Dr. Sahar Mohammed Salman (Proximus Journal Publishing, 2025)
The study aimed at employing platelet-rich plasma (PRP) injection as a modern treatment strategy to enhance the range of motion and alleviate discomfort in basketball players with rotator cuff injuries in the shoulder joint. The research sample consisted of five basketball players with rotator cuff injuries in the shoulder joint, with a mean age of 24.55 ± 0.54 years, an average weight of 75.84 ± 9.16 kg, and a mean height of 183.40 ± 5.24 cm. Specialized physicians assessed their injuries. Platelet-rich plasma injections were provided only once, and the athletes were constrained from exercise and from using the afflicted joint for three days following the injection. Subsequently, they contributed to moderate-intensity training for two weeks and returned to the specified training load after three weeks, with watchful nursing of pain and their condition. The shoulder joint’s range of motion was evaluated following the guidelines of the American Academy of Orthopedic Surgeons (AAOS), while pain intensity was estimated using a visual analog scale (VAS) containing 10 points. The measurements were gained prior to the injection (pre-test) and six weeks subsequent to it (post-test). The Statistical Package for the Social Sciences (SPSS) was employed to generate the research findings. The study findings indicated that the platelet-rich plasma (PRP) injection method significantly improved the range of motion, alleviated pain levels, and restored shoulder joint function in basketball players, without opposing side effects, and did not obstruct their training schedule.
Keywords: Platelet-Rich Plasma; Rotator Cuff Injuries; Range of Motion; Musculoskeletal Pain